Sistem Pakar Screening Awal Gangguan Kesehatan Mental Social Anxiety Disorder Menggunakan Metode Forward Chaining Berbasis Website - Naufal Athallah Hidayat; Anis Mirza (CV. Shofanah Media Berkah, 2023)
Anxiety that is more can cause a person to have difficulty controlling his thoughts, difficulty concentrating, feeling helpless, and discomfort that interferes with life and daily activities. Excessive anxiety is a psychological disorder called anxiety disorder. Anxiety disorder is a mental health disorder that is continuously characterized by the emergence of excessive fear and worry, feeling constantly watched, judged, and humiliated by everyone. One type of anxiety disorder is social anxiety disorder or called social anxiety disorder. Social anxiety disorder itself is an extraordinary feeling of anxiety or fear of social situations or interactions with other people because of fear of other people's judgment of themselves. There are several problems regarding social anxiety disorder, which is that it is still unknown how many people know about social anxiety disorder, there is still a lack of education to the public about social anxiety disorder, and there are no supporting media for the community, how do they find out whether they are indicated by a social anxiety disorder or not. With the problems that exist in the community, a solution is created in the form of educational media and media for early detection or early screening of website-based symptoms of social anxiety disorder, which can help people to get to know what social anxiety disorder is and as a medium for the community to can find out whether he is indicated or not about social anxiety disorder.